The Neutron Facility at NCSR "Demokritos"- Implementation in the Case of the 232Th(n,2n) and 241Am(n,2n) Reactions - Vlastou, R.; Papadopoulos, C. T.; Perdikakis, G.; Kokkoris, M.; Kossionides, S.; Karamanis, D.; Assimakopoulos, P. A. (HNPS Advances in Nuclear Physics, 2020)
In the 5.5 MV tandem T11/25 Accelerator Laboratory of NCSR "Demokritos" monoenergetic neutron beams can be produced in the energy ranges 120-650 keV, 4-11.5 MeV and 16-20.5 MeV by using the 7Li(p,n), 2H(d,n) and 3H(d,n) reactions, respectively. The corresponding beam energies and ions delivered by the accelerator, are 1.92-2.37 MeV protons, 0.8-9.6 MeV deuterons and 0.8-3.7 MeV deuterons, for the three reactions, respectively. Experimental results for neutron energies from threshold up to 11.5 MeV and at 17.1 MeV will be given for the 232Th(n,2n)231Th reaction, while for the 241 Am(n,2n)240 Am reaction, preliminary cross section data at 10.4, 10.6 and 17.1 MeV will be discussed. In the framework of the CERN n-TOF collaboration, the cross section of these reactions have been measured relative to the 197Au(n,2n)196Au, 27Al(n,a)24Na and 93Nb(n,2n) reaction cross sections, by using the activation method. In addition to the experimental work, theoretical Statistical model calculations are being carried out using the computer code STAPRE/F. The results are compared to the experimental data.